2012
DOI: 10.1002/pip.2158
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of multi‐junction solar cell parameters

Abstract: The paper deals with the parameter estimation of InGaP/GaAs/Ge multi‐junction solar cell and is based on minimizing the difference between the measured I–V and the theoretical I–V characteristics—the objective function. The parameter estimation was first performed on a multi‐junction solar cell represented by a single‐diode model containing eight parameters: five conventional parameters and three additional parameters for the negative diode breakdown voltage. An extended model is also presented for detailed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Despite the fact that several electrical models and experimental procedures for MJ solar cells have been described thoroughly in literature (Ben Or and Appelbaum, 2013;Dominguez et al, 2010;Fernández et al, 2013;Fernandez et al, 2013b;Kinsey and Edmondson, 2009;Kinsey et al, 2008;Rodrigo et al, 2013;Segev et al, 2012;Siefer and Bett, 2014) which included the spectrum and irradiance dependence, the challenge to develop an integrated thermal-electrical model which predicts the cell temperature and includes the cooling needs is still unsolved. This study builds on a methodology (Theristis and O'Donovan, 2014) which considered a constant spectral response at 25°C and AM1.5D.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Despite the fact that several electrical models and experimental procedures for MJ solar cells have been described thoroughly in literature (Ben Or and Appelbaum, 2013;Dominguez et al, 2010;Fernández et al, 2013;Fernandez et al, 2013b;Kinsey and Edmondson, 2009;Kinsey et al, 2008;Rodrigo et al, 2013;Segev et al, 2012;Siefer and Bett, 2014) which included the spectrum and irradiance dependence, the challenge to develop an integrated thermal-electrical model which predicts the cell temperature and includes the cooling needs is still unsolved. This study builds on a methodology (Theristis and O'Donovan, 2014) which considered a constant spectral response at 25°C and AM1.5D.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Some investigators have proposed different methods to obtain the parameters of the subcells by making different assumptions and simplifications. Examples of extraction methods based on the SEM scheme can be found in the literature [46,55,59,[66][67][68] as can results from those based on the DEM scheme [59,[69][70][71]. It is important to note that these studies usually estimate the parameters at a particular set of operating conditions.…”
Section: Influence Of Optical Concentrationmentioning
confidence: 99%
“…It was reported that the solar cell one-diode equivalent circuit is able to characterize the experimental I-V curves of a triple-junction solar cell in an HCPV receiver [35]. This equivalent circuit depends on five parameters: photocurrent (I ph ), saturation current (I 0 ), diode ideality factor (m), series resistance (R s ) and shunt resistance (R sh ).…”
Section: Unshaded Receiver Blockmentioning
confidence: 99%